Association of Prolyl Oligopeptidase with Conventional Neurotransmitters in the Brain - Peltonen, Iida; T. Myohanen, Timo; T. Mannisto, Pekka (CNS & Neurological Disorders - Drug Targets, 2011)
Prolyl oligopeptidase (POP), is an 80-kDa serine protease that hydrolyzes peptides smaller than 30-mer at the carboxyl side of an internal proline-residue. POP is commonly believed to cleave a number of neuropeptides claimed to be involved in learning, memory and mood. While the support to the neuropeptide cleavage theory has been declining, new data suggest novel functions for POP, e.g. as a regulator of protein secretion, α-synuclein aggregation and cell proliferation/differentiation. Intriguingly, many of these novel functions may not depend on the hydrolytic activity of POP. One of the new roles is an involvement of POP in neurotransmission. Indeed, POP has been associated with a variety of different neurotransmitters. According to our previous results, POP is located in GABAergic and cholinergic neurotransmitter systems and in short glutamatergic projection neurons between cortex and thalamus. Based on these findings, POP may be involved in inhibitory and excitatory signal transmission and in the thalamocortical and corticothalamic signalling in the brain. It has also been shown that POP inhibition can affect the functions of neurotransmitters and that the ligands of neurotransmitter receptors can alter the activity of POP. Thus, there is a connection between the neurotransmitters and POP, although the mechanisms and the functional significance of this linkage are still unknown. Here, we will review the data about the connections of POP with conventional neurotransmitter systems and provide an overview of the role of POP in neurotransmission.
Keywords: Serotonin